Racial disparities in fifth‐grade sun protection: Evidence from the Healthy Passages study. Issue 5 (2nd July 2018) - Correnti, Christina M.; Klein, David J.; Elliott, Marc N.; Veledar, Emir; Saraiya, Mona; Chien, Alyna T.; Schwebel, David C.; Mrug, Sylvie; Tortolero, Susan R.; Cuccaro, Paula M.; Schuster, Mark A.; Chen, Suephy C.
Abstract: Background/Objectives: Despite rising skin cancer rates in children, multiple studies reveal inadequate youth sun‐protective behavior (eg, sunscreen use). Using Healthy Passages data for fifth‐graders, we set out to determine sunscreen adherence in these children and investigated factors related to sunscreen performance. Methods: Survey data were collected from 5119 fifth‐graders and their primary caregivers. Logistic regression was used to assess associations between sunscreen adherence and performance of other preventive health behaviors (eg, flossing, helmet use) and examine predictors of sunscreen adherence. Analyses were repeated in non‐Hispanic black, Hispanic, and non‐Hispanic white subgroups. Results: Five thousand one hundred nineteen (23.4%) children almost always used sunscreen, 5.9% of non‐Hispanic blacks (n = 1748), 23.7% of Hispanics (n = 1802), and 44.8% of non‐Hispanic whites (n = 1249). Performing other preventive health behaviors was associated with higher odds of sunscreen adherence (all P < .001), with the greatest association with flossing teeth (odds ratio = 2.41, 95% confidence interval = 1.86‐3.13, P < .001). Factors for lower odds of sunscreen adherence included being male and non‐Hispanic black or Hispanic and having lower socioeconomic status. School‐based sun‐safety education and involvement in team sports were not significant factors. Conclusion: Our data confirm low use of sun protection among fifth‐graders. Future research should explore how public health success in increasing prevalence of other preventive health behaviors may be applied to enhance sun protection messages. Identifying risk factors for poor adherence enables providers to target patients who need more education. Improving educational policies and content in schools may be an effective way to address sun safety.